L'autre est un Je - Abramovici, Serge (2014)
The 'differentness' of the poets of the Antilles cannot be attributed to an exotic cultural — thematic or cultural — point of reference; rather it structures the language of the respective texts in their minimum units, rhythm, syntax, prosody, etc.. The perception of the 'Other' points us to our own obscurity from which only the crossing of races — or rather, the linguistic crossing of races - can liberate us.